STRATEGI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN BOJONEGORO DALAM PENERAPAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) DI KABUPATEN BOJONEGORO - Nisa Safaatin; Ertien Rining Nawangsari (Jurnal Ilmu Sosial dan Ilmu Politik)
The Electronic Based Government System (SPBE) has been implemented in Bojonegoro Regency. In its implementation, there are several problems, namely the SPBE index, which is still not optimal, lack of IT knowledge in human resources, and infrastructure, which is still uneven. This research aims to determine the strategy of the Bojonegoro Regency Communication and Information Service in implementing SPBE in the Bojonegoro Regency. The focus of this research uses SOAR analysis by paying attention to 4 factors, namely Strength, Opportunities, Aspiration, and Results. This research was conducted in March 2023. The research methods used were structured interviews with several informants, observation by observing research objects, and documentation by searching for information in the form of notes, reports and news where the data obtained was then analyzed using SOAR analysis. The research results show that there are 4 strategies, namely the SA strategy, SR strategy, OA strategy, and OR strategy. The SA strategy that can be implemented is to improve the quality of human resources by providing training and technical guidance so that the implementation of SPBE can be carried out optimally. The SR strategy that can be implemented is by adding and strengthening infrastructure that can support the implementation of SPBE better. An OA strategy that can be implemented is by conducting regular training and technical guidance with more targets. The OR strategy that can be carried out is by making improvements to things that are still not optimal.